Gene editing and therapy - A new tool: CRISPR/Cas9 - Ashok M. Patil (Al Ameen Medical College, 2019)
One of the most important scientific discoveries of the past few years is a powerful new gene editing technology known as CRISPR/Cas9. Gene editing opens the door to treatments for an array of diseases, and holds tremendous potential to treat various inherited & acquired diseases.